Handbook on material and energy balance calculations in material processing - Morris, Arthur E., 1935-; Fine, H. Alan.; Geiger, Gordon Harold, 1937-; Fine, H. Alan. (Hoboken, N.J. : Wiley-TMS, 2011)
"This book approaches the subject of material and energy balances from two directions. First, it emphasizes the fundamental principles of the conservation of mass and energy, and the consequences of these two principles. Second it applies the techniques of computational chemistry to materials processing, and introduces new software developed by the author especially for material and heat balances. The third edition reflects the changes in the professional engineer's practice in the last 30 years, reflecting the dramatic shift away from metallurgical engineering and the extractive industry towards materials engineering. A large and growing number of recent graduates are employed in such fields as semiconductor processing, environmental engineering, and the production and processing of advanced and exotic materials for aerospace, electronic and structural applications. The advance in computing power and software for the desktop computer has significantly changed the way engineers make computations, and the biggest change comes from the computational approach used to solve problems. The spreadsheet program Excel is used extensively throughout the text as the main computational "engine" for solving material and energy balance equations, and for statistical analysis of data. The use of Excel and the introduction of the add-in programs enables the study of a range of variables on critical process parameters, and emphasis is placed on multi-device flowsheets with recycle, bypass, and purge streams whose material and heat balance equations were previously too complicated to solve by the normally-used hand calculator. The Excel-based program FlowBal helps the user set up material and heat balance equations for processes with multiple streams and units"--
"This book approaches the subject of material and energy balances from two directions"--
Rev. ed. of: Handbook on material and energy balance calculations in metallurgical processes. 1979.
.
Includes bibliographical references (p. [605]) and index.
Keywords: Chemical processes -- Mathematical models -- Handbooks, manuals, etc; Manufacturing processes -- Mathematical models -- Handbooks, manuals, etc; Chemical processes -- Mathematical models -- Handbooks, manuals, etc; Materials -- Handbooks, manuals, etc; Phase rule and equilibrium -- Handbooks, manuals, etc; Heat balance (Engineering) -- Mathematics -- Handbooks, manuals, etc; Conservation laws (Physics) -- Mathematics -- Handbooks, manuals, etc; TECHNOLOGY & ENGINEERING / Material Science